On Certain Disputable and/or Unexplained Forms of the Imperative in Modern Armenian Dialects - Avetyan, Sargis (Bulletin of Yerevan University B: Philology, 2024)
An attempt is made to demonstrate that the historical development of forms of the imperative in modern Armenian dialects has been quite a complex process, significantly influenced by the intense interplay of various analogical and phonetic changes. These changes have frequently obscured the original situation and the synchronic morphological relationships between different formation types of the imperative, as well as the relationship between the imperative and the aorist. On the other hand, because dialectologists have often overlooked relevant evidence from other dialects when describing a particular dialect, this has largely hindered scholars from gaining a deeper understanding of the issues being examined and from thoroughly and accurately investigating the linguistic material. In addition, it should be noted that the investigation of modern Armenian dialects has, for the most part, been of a synchronic-descriptive nature. As a result, the joint effect of the above circumstances has frequently led to various misunderstandings and misinterpretations. Of course, examining all such controversial issues would be going too far. Therefore, this article will address only some of the most questionable interpretations and/or unexplained phenomena.
Keywords: forms of the imperative; modern Armenian dialects; the intense interplay of various analogical and phonetic changes; the synchronic morphological relationships; imperative; aorist